The effect of triple CFTR modulator therapy and azithromycin on ion channels and inflammation in cystic fibrosis - Suhad Bani Melhim; Lisa E.J. Douglas; James A. Reihill; Damian G. Downey; S. Lorraine Martin (ERJ Open Research)
Background Inflammation in cystic fibrosis (CF) airways is difficult to treat with well-established regimens often including azithromycin (AZ) as an immunomodulatory drug. As AZ has been reported to require CF transmembrane conductance regulator (CFTR) to be able to reduce interleukin (IL)-8 and given the emergence of highly effective CFTR “triple” modulator therapy (elexacaftor/tezacaftor/ivacaftor; ETI), the aim of this study was to investigate the effect of AZ and ETI, singly and in combination, on ion channel activity and to assess the potential anti-inflammatory effects. Methods Electrophysiological assessment of ETI and AZ was performed on three-dimensional cultures of primary CF human bronchial epithelial (HBE) cells using a Multi Trans-Epithelial Current Clamp. IL-8 from NuLi-1 (non-CF) and CuFi-1 (CF) cells treated with AZ was measured by ELISA. Inflammatory mediators from primary CF HBE cells exposed to tumour necrosis factor-α in the presence of AZ, ETI and their combination, were screened using the Proteome Profiler™ Human Cytokine Array Kit, with selected targets validated by ELISA. Results AZ did not alter CFTR chloride efflux, nor did it have any synergistic/antagonistic effect in combination with ETI. AZ reduced IL-8 in NuLi-1 but not CuFi-1 cells. The Proteome Profiler™ screen identified several disease-relevant cytokines that were modulated by treatment. Subsequent analysis by ELISA showed IL-8, IL-6, CXCL1 and granulocyte–macrophage colony-stimulating factor to be significantly reduced by treatment with ETI, but not by AZ. Conclusions Incorporating ETI into the standard of CF care provides an opportunity to re-evaluate therapeutic regimens to reduce treatment burden and safely discontinue chronic treatments such as AZ, without loss of clinical benefit. Identification of redundant treatments in the era of CFTR modulation may improve medication adherence and overcome potential adverse effects associated with the chronic use AZ and other drugs.